Handbook of human factors and ergonomics - Salvendy, Gavriel (Wiley, 1997)
In orchestrating this book, Dr. Salvendy invited contributions from more than 100 of the foremost authorities around the world. Each of its 60 chapters was reviewed by an international advisory panel comprised of some of today's leading figures in human factors and ergonomics. While each chapter establishes the theoretical and empirical foundations of the subject under discussion, the book's approach is primarily